Role of MRP transporters in regulating antimicrobial drug inefficacy and oxidative stress-induced pathogenesis during HIV-1 and TB infections - Roy, Upal; Barber, Paul; Tse Dinh, Yuk ching; Batrakova, Elena V.; Mondal, Debasis; Nair, Madhavan (Frontiers in Microbiology, 2015)
Multi-Drug Resistance Proteins (MRPs) are members of the ATP binding cassette (ABC) drug-efflux transporter superfamily. MRPs are known to regulate the efficacy of a broad range of anti-retroviral drugs (ARV) used in highly active antiretroviral therapy (HAART) and antibacterial agents used in Tuberculus Bacilli (TB) therapy. Due to their role in efflux of glutathione (GSH) conjugated drugs, MRPs can also regulate cellular oxidative stress, which may contribute to both HIV and/or TB pathogenesis. This review focuses on the characteristics, functional expression, and modulation of known members of the MRP family in HIV infected cells exposed to ARV drugs and discusses their known role in drug-inefficacy in HIV/TB-induced dysfunctions. Currently, nine members of the MRP family (MRP1-MRP9) have been identified, with MRP1 and MRP2 being the most extensively studied. Details of the other members of this family have not been known until recently, but differential expression has been documented in inflammatory tissues. Researchers have found that the distribution, function, and reactivity of members of MRP family vary in different types of lymphocytes and macrophages, and are differentially expressed at the basal and apical surfaces of both endothelial and epithelial cells. Therefore, the prime objective of this review is to delineate the role of MRP transporters in HAART and TB therapy and their potential in precipitating cellular dysfunctions manifested in these chronic infectious diseases. We also provide an overview of different available options and novel experimental strategies that are being utilized to overcome the drug resistance and disease pathogenesis mediated by these membrane transporters.